(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
The problem of additional water intake from pressure horizon of Arevic intermountain basin is solved, based on evaluation of field investigations results. The problem of three-layered geofiltration medium is solved on JBM computer using "Topaz" program. The possibility of additional intake, about 2,2 times as must as present 830 l/s, is proved by means of mathematical modelling. The estimated decreasing of level is less than maximum permitted level of pressure water in wells. The number of water intake wells, their yields, efficient location, duration of water intake and possible guantity of taken water are also evaluated.